The influence of animation video media on the Arabic vocabulary mastery of grade VIII students of MTs Asnawiyah - Siti Zakkiyatul Fahiroh; Desky Halim Sudjani; Fikni Mutiara Rachma (Mitra Palupi, 2021)
Background: Students' difficulties in learning Arabic are due to their lack of mastery of Arabic vocabulary and this affects other Arabic language skills. The learning that has been less interactive so far due to the lack of variety of teachers in the use of learning media, improvements can be made by utilizing existing media to assist the learning process Purpose: This study aims to determine the effect of the use of animated video media on the Arabic vocabulary mastery of class VIII MTs Asnawiyah. Design and methods: The method used in this study is the quantitative method, the type of experimental research and the research design using a quasi-experimental design with a pretest-posttest control design. Data collection techniques by means of observation, interviews, documentation and tests, namely pretest and posttest in the experimental class and control class with a total sample of 86 samples. Results: The final results of this study indicate that there is an influence of animated video media on the vocabulary mastery of class VIII students of MTs Asnawiyah, this can be shown from the results of the study which were measured using Mann Whitney and obtained a sig value of 0.000 where a sig value of 0.000 <0.05.